Mechanical modelling quantifies the functional importance of outer tissue layers during root elongation and bending - Dyson, Rosemary J.; Vizcay-Barrena, Gema; Band, Leah R.; Fernandes, Anwesha N.; French, Andrew P.; Fozard, John A.; Hodgman, T. Charlie; Kenobi, Kim; Pridmore, Tony P.; Stout, Michael; Wells, Darren M.; Wilson, Michael H.; et al. (Wiley, 2014)
Root elongation and bending require the coordinated expansion of multiple cells of different types. These processes are regulated by the action of hormones that can target distinct cell layers. We use a mathematical model to characterise the influence of the biomechanical properties of individual cell walls on the properties of the whole tissue.